Makna Musibah dan Derivasinya dalam Tafsir Fī Zhilālil Qur’ān, Sayyid Quthb - Mastur, Ali; Adiguna, Dimas Yediya Satria (Ikatan Dai Indonesia, 2024)
Sayyid Quthb, a contemporary mufassir who is productive in producing scientific works in various disciplines. One of them is the interpretation of Fī Zhilālil Qur'ān. The problem raised in this study is How does Sayyid Quthb view disasters? This study uses a descriptive-analytical method, with a library research nature based on the interpretation of Fī Zhilālil Qur'ān as a primary source. With the conclusion that the meaning of disaster is everything that befalls, be it good or bad. Both come from Allah SWT and are part of Allah SWT's planning in the creation of the universe and humans are one of Allah SWT's weak creatures, needing love and guidance from Allah SWT to achieve happiness in life. The practical benefits of this study are that a correct understanding of the meaning of disasters makes it easier for humans to be patient and can be used as an effective approach in strengthening mental resilience and steadfastness in facing disasters.